(untitled) (Revista Espacio Regional, 2021)
In the global context, the phenomenon of hunger is usually related to insufficient food and its inaccessibility. But this reality is faced with record yields and food waste. Food waste can occur in several stages, either in production, logistics, marketing and consumption. In Brazil, many foods are excluded from the market at the time of marketing, especially in supply centers for non-compliance to the laws that focus mainly on aesthetics, better known as quality standards. This article brings elements to question the way how is this classification. The proposal is to extrapolate the vision about the quality bringing it to a wide perspective, beginning with the production system, emphasizing the ecological balance, ethics, waiver of transgenic pesticides and seeds, respect for the cycle of nature and the cultural practices of production and consumption. Therefore, it takes as a basis the model of production and consumption in agroecology guided to reflect on this classification, with a strategy that strengthens and supports the Sovereignty and Food and Nutritional Security. It is suggested that forward vision is overcome the aesthetics of food to achieve untying the framework standardization-nature and thus reduce food waste.